(untitled) (Research, Society and Development, 2020)
The low availability of forage due to water scarcity and the effect of climate change are problems faced by rural producers in semiarid regions. To circumvent these effects, research shows the importance of using species that are adapted to environmental conditions. Among these species, forage cactus is an important food for ruminant diets, highly acceptable, rich in energy, and high water content, in addition to its low-cost implantation in the field. Millet is another species used, as it has tolerance to water and salt stresses, in addition to being a useful food for supplementation along with forage cactus. The use of agricultural practices such as irrigation, mulch and intercropping can assist in the production system of these crops. In addition, the application of agrometeorological parameters is relevant to ensure the best planning and agricultural decision-making. In this review, the objective was to address agronomic practices, statistical analysis, and agrometeorological indicators used in research aimed at forage cactus and millet crops in production systems. The research was carried out in the bibliographic bases of Scopus, ScienceDirect, Mendeley, and Google Scholar. Agricultural practices minimum use of irrigation, mulch, and intercropping are essential in the cultivation systems of forage cactus and millet. In conjunction with the management of these cultures, the use of agrometeorological indicators linked to multivariate analysis allows for better planning and decision making in production.